Antimicrobial, anticancer, and antioxidant compounds from premna resinosa growing in Saudi Arabia - Albadawi, Dina A.; A. Mothana, Ramzi Ahmed; M. Khaled, Jamal; Ashour, Abdelkader Elbadawy Abbas; Kumar, Ashok; Ahmad, Sheikh Fayaz; Al-Said, Mansour Sulaiman; Al-Rehaily, Adnan Jathlan; M. Almusayeib, Nawal (Taylor and Francis Ltd., 2017)
CONTEXT: Premna resinosa (Hochst.) Schauer (Lamiaceae) is used in many places to treat bronchitis, respiratory illness and convulsions of the rib cage.